A new paradigm for muscle contraction - Herzog, Walter; Powers, Krysta; Johnston, Kaleena; Duvall, Mike (Frontiers in Physiology, 2015)
For the past 60 years, muscle contraction had been thought to be governed exclusively by the contractile filaments, actin and myosin. This thinking explained most observations for concentric and isometric, but not for eccentric muscle contractions. Just over a decade ago, we discovered that eccentric contractions were associated with a force that could not be assigned to actin and myosin, but was at least in part associated with the filamentous protein titin. Titin was found to bind calcium upon activation, thereby increasing its structural stability, and thus its stiffness and force. Furthermore, there is increasing evidence that the proximal part of titin binds to actin in an activation- and force-dependent manner, thereby shortening its free length, thus increasing its stiffness and force. Therefore, we propose that muscle contraction involves three filaments, actin, myosin and titin, and that titin regulates force by binding calcium and by shortening its spring length by binding to actin.